Auditory Efferent System: New Insights from Cortex to Cochlea - Ana B. Elgoyhen (Frontiers Research Topics, 2016)
The main function of the sensory systems is the transducing of external stimuli into bioelectrical signals, which are conducted through afferent pathways from sensory epithelia to the brain. However, it is known that descending projections are ubiquitous in the different sensory modalities, and in the case of auditory efferents connect the cerebral cortex with sensory receptor cells. Several functions have been attributed to the efferent system, including protection to acoustic trauma, unmasking of auditory stimuli in background noise, balance of interaural sensitivity and some cognitive functions like modulation of cochlear sensitivity during selective attention to auditory or visual stimuli. In addition there is evidence of a possible involvement of the efferent system in the etiology or treatment of some clinical pathologies like tinnitus. In this e-book, entitled "Auditory Efferent System: New Insights from Cortex to Cochlea", we aimed to give an overview of the advances concerning the descending projections from the auditory cortex to subcortical nuclei and the olivocochlear system. In addition, different theoretical proposals of efferent functions are presented. We think that this e-book is an important contribution to the understanding of the efferent system in mammals, merging auditory-cortex literature with studies performed in the olivocochlear system.